2004
DOI: 10.1128/cdli.11.5.977-982.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Gene Expression Profiles of Peripheral Blood Mononuclear Cells Do Not Reflect Those of T-Lymphocyte Subsets

Abstract: Advances in microarray technology have allowed for the monitoring of thousands of genes simultaneously. This technology is of particular interest to immunologists studying infectious diseases, because it provides tremendous potential for investigating host-pathogen interactions at the level of immune gene expression. To date, many studies have focused either on cell lines, where the physiological relevance is questionable, or on mixed cell populations, where the contributions of individual subpopulations are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Unlike previous microarray studies that were conducted with either whole PBMCs 41,42 or a specific cell type (CD4 or CD8 ϩ T cells), [43][44][45][46] microarray analysis in our study was performed with FACS-sorted, antigen-specific CD4 populations. Microarray analysis revealed that CMV-specific CD4 T cells activated a broad array of innate antiviral genes or pathways that have known anti-HIV or SIV activities.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous microarray studies that were conducted with either whole PBMCs 41,42 or a specific cell type (CD4 or CD8 ϩ T cells), [43][44][45][46] microarray analysis in our study was performed with FACS-sorted, antigen-specific CD4 populations. Microarray analysis revealed that CMV-specific CD4 T cells activated a broad array of innate antiviral genes or pathways that have known anti-HIV or SIV activities.…”
Section: Discussionmentioning
confidence: 99%
“…The use of PBMCs may limit interpretations because of dilution and may not reflect the gene profile from individual subpopulations [29]. It has been suggested that researchers limit studies using PBMCs in favor of those within subpopulations [30]. …”
Section: Gene Array Technology In a Nutshellmentioning
confidence: 99%
“…Of particular interest was the potential contribution of CD4 ϩ vs CD8 ϩ T cells, as these subsets within PBMC are known to have distinct gene expression profiles (59).…”
Section: Gene Expression Profiling Of Inhalant Allergen Driven Gene Ementioning
confidence: 99%
“…Data expressed on the log 2 scale. Table II The data of primary interest in Table II are those derived from CD4 ϩ and CD8 ϩ populations in which enrichment for responder cells may be expected to reduce the background noise relative to unfractionated PBMC (59,61). Our principal focus was upon 12/24 h time points which encompass the peak of the early Th2-associated cluster, and where specified genes which did not validate at these time points were followed up further in 48-h samples.…”
Section: Qrt-pcr Validation Of Microarray Findingsmentioning
confidence: 99%